The Role of Ischemia Reperfusion Damage on Renal Transplant, what are the new treatments? - Otukesh, Hasan; Hoseini, Rozita; Rahimzadeh, Nahid; Hosseini, Sara; Ahmadpoor, Pedram; Javadilarijani, Faezeh (Journal of Pediatric Nephrology, 2013)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –><span style="font-size: 10.0pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-fareast-font-family: TimesNewRomanPSMT; mso-hansi-theme-font: major-latin; mso-bidi-font-family: TimesNewRomanPSMT; color: #76923c; mso-themecolor: accent3; mso-themeshade: 191; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">How to Cite This Article<span style="font-size: 10.0pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-fareast-font-family: TimesNewRomanPSMT; mso-hansi-theme-font: major-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">: <span style="font-size: 10.0pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: major-latin; mso-bidi-font-family: Times-Roman; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Otukesh H, Hoseini R, Rahimzadeh N, Hosseini S, Ahmadpoor P, Javadi Larijani F<span style="font-size: 10.0pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-fareast-font-family: TimesNewRomanPSMT; mso-hansi-theme-font: major-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">. <span style="font-size: 10.0pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: major-latin; mso-bidi-font-family: Times-Bold; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The role of Ischemia reperfusion damage on renal transplant, what are the new treatments?<span style="font-size: 10.0pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-fareast-font-family: TimesNewRomanPSMT; mso-hansi-theme-font: major-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> J Ped. Nephrology 2013 July;1(1):1-7. Ischemia reperfusion damage usually occurs after renal transplantation. These injuries can stimulate the innate immune system, trigger an inflammatory response and ultimately activate the adaptive immune system. These events may result in rejection, graft fibrosis and chronic allograft nephropathy. Different mechanisms contribute to innate immune system activation following ischemia reperfusion injury in renal transplants. Some of these mechanisms are known and described by investigators while the remaining are still unknown. To clarify the precise mechanisms underlying the innate immune system activation and rejection progression helps us to plan therapeutic protocols to reduce immunologic responses to ischemic events and to improve the graft function and outcome. In this review, we will discuss how innate and adaptive immune systems are activated during an ischemic insult and thereafter discuss related therapeutic interventions to block the activating pathways. <span style="font-size: 10pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-hansi-theme-font: major-latin; mso-bidi-language: AR-SA; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-fareast-font-family: ’Times New Roman’; mso-fareast-theme-font: minor-fareast; mso-fareast-language: EN-US; mso-ansi-language: EN-US;">Keywords:<span style="font-size: 10pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-hansi-theme-font: major-latin; mso-bidi-language: AR-SA; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-fareast-font-family: ’Times New Roman’; mso-fareast-theme-font: minor-fareast; mso-fareast-language: EN-US; mso-ansi-language: EN-US;"> Ischemia; Renal transplantation; Reperfusion.<span style="font-size: 12pt; line-height: 115%; font-family: "Cambria","serif"; mso-ascii-theme-font: major-latin; mso-hansi-theme-font: major-latin; mso-bidi-language: AR-SA; mso-bidi-font-family: Arial; mso-bidi-theme-font: minor-bidi; mso-fareast-font-family: ’Times New Roman’; mso-fareast-theme-font: minor-fareast; mso-fareast-language: EN-US; mso-ansi-language: EN-US;">